Discourse Representation of Dialogic Principles in Teacher-Learner Communication - Zarichna, Olena (East European Journal of Psycholinguistics, 2016)
This article presents a consideration of the problem of discourse representation of pedagogic dialogue in teacher-learner interactions. The functional parameters inherent in the pedagogical process condition an understanding of pedagogic dialogue as a personality-centered type of communication based on the principles of value oriented treatment, alterocentrism, personal inclusion, metaposition of the teacher, personal authenticity and thereby distinguished from the liberal and democratic paradigm. As a special challenge for this study there has been elaborated a scheme of dialogic discourse specified in corresponding discourse patterns, markers and speech acts. The focus is made on those discourse elements featuring the principles of pedagogic dialogue. In the course of inclusive observation conducted on the basis of this scheme there were determined three basic communication styles featuring different levels of communicative disposition: dialogic, semi-dialogic and monologic. The statistics reveal comparatively low percentage of young teachers possessing dialogic dispositions and strategies in pedagogic communication which calls for certain alterations in the system of teacher training as well as personality development of future educators.ReferencesБалл Г. А. Современный гуманизм и его диалогические универсалии / Г. А. Балл //Гуманітарні науки. – 2001. - № 2. – С. 4–10.Ball, G. (2001). Sovremennyi gumanism i ego dialogicheskiye universaliyi [Modernhumanism and its dialogic universal statements]. Gumanitarni Nauky, 2, 4–10.Бахтин М. М. Эстетика словесного творчества / М. М. Бахтин. – М.: Искусство, 1979.Bakhtin, M. M. (1979). Estetika Slovesnogo Tvorchestva [Aesthetics of Verbal Art].Moscow: Iskusstvo.Бубер М. Диалог // М. Бубер. Два образа веры. – М.: Республика, 1995. – С.158-232.Buber, M. (1995). Dialog. Dva obraza very. [Dialogue. Two images of faith]. Moscow:Respublika.Бирюкова Г. М. Специфика диалогических отношений в образовательном процессе[Электронный ресурс]. – Режим доступа: http://anthropology.ru/ru/ texts/biryukova/educdial_33.htmlBiriukova, G. Spetsifika dialogicheskih otnoshenij v obrazovatelnom protsesse. Retrievedfrom: http://anthropology.ru/ru/texts/biryukova/educdial_33.htmlВолодько Н. В. Диалогическое общение как фактор преодоления дезадаптации ребенка кшколе: дисс….канд. псих. наук: 19.00.07 / Володько Наталия Валерьевна. – Н. Новгород,1999.Volodko, N. V. (1999). Dialogicheskoye obshcheniye kak factor preodoleniya dezadaptatsiirebionka k shkole [Dialogic communication as a factor of overcoming children'sdisadaptation to school]. NizhniyNovgorod.Каминская М. В. Методика экспертной оценки диалогического взаимодействия учителя иученика на уроке развивающего образования / М. В. Каминская. – М.: Изд-во “Про-Пресс”,2004.Kaminskaya, M. (2004). Metodika ekspertnoi otsenki dialogicheskogo vzaimodeistviyauchitelia i uchenika na uroke razvivayushchego obrazovaniya [Methodology of expertevaluation of dialogic teacher-learner interaction at a lesson of developmental education].Moscow: Pro-Press.Лабунская Н. А. Студент в диалоге с преподавателем [Электронный ресурс] /Н. А. Лабунская. – Режим доступа:http://anthropology.ru/ru/texts/labunsk/educdial_44.html Labunskaya, N. A. Student v dialoge s prepodavatelem. Retrieved from:http://anthropology.ru/ru/texts/labunsk/educdial_44.htmlПавлова Н.П. Интерактивный аспект дискурса: подходы к исследованию /Н. П. Павлова // Психологический журнал. – 2005. – Том 26. – №4. – С. 66 – 76.Pavlova, N. P. (2005). Interaknivnyi aspekt diskursa: podhody k issledovaniyu [Interactiveaspect of discourse: approaches to investigation], Psihologicheskiy zhurnal, 2005.Ушакова В. В. Педагогические условия формирования обобщенных конструктивныхумений у будущих педагогов профессионального обучения: дисс. … канд. пед. наук:13.00.08 / Ушакова Вероника Валерьевна. – Челябинск, 2003. – 248 с.Ushakova, V. V. (2003). Pedagogicheskiye usloviya [Pedagogic conditions of formation ofcomprehensive constructive abilities in future pedagogues of professional education].Cheliabinsk.Burbules, N. C. (2001). Theory and research on teaching as dialogue. Handbook ofResearch on Teaching, 4th Edition., Virginia Richardson, Ed. Washington, D. C:American Educational Research Association. 1102-1121.Sinclair, J.McH. and Coulthard, R.M. (1975). Towards an Analysis of Discourse. In: TheEnglish Used by Teachers and Pupils. (pp. 19-60). Oxford: Oxford University Press.